Antioxidant Aryl-Substituted Phthalan Derivatives Produced by Endophytic Fungus Cytospora rhizophorae - Liu, Hongxin; Liu, Zhaoming; Zhang, Yanjiang; Chen, Yuchan; Wang, Huan; Tan, Haibo; Zhang, Weimin (Frontiers in Chemistry, 2022)
Six new phthalan derivatives cytorhizophins D-I (1-6) as well as three known derivatives cytorhizophin C, pestacin and rhizophol B were isolated from Cytospora rhizophorae. Among them, cytorhizophins D-E (1-2) and F-G (3-4) were two pairs of diastereoisomers, all of them featuring a 1-phenyl-1,3-dihydroisobenzofuran scaffold with a highly oxygenated O-linked isopentenyl unit. Besides, cytorhizophins H-I (5-6) represent the first examples of phthalide family with fascinating 6/6/6/5 tetracyclic ring system fusing as unprecedented furo [4,3,2-kl]xanthen-2 (10bH)-one skeleton. The structures of the new phthalan derivatives were extensively confirmed by detail spectroscopic analysis. The partial absolute configurations of compounds 1-6 were established through electronic circular dichroism (ECD) calculations. Moreover, compounds 1-4 showed remarkable antioxidant activities with EC50 values ranging from 5.86 to 26.80 μM, which were better than or comparable to that of ascorbic acid (positive control).